A fully integrated zero-IF transceiver for GSM-GPRS quad-band application. - Duvivier, E.
A fully integrated GSM/GPRS quad-band transceiver is presented. It includes the receiver, the transmitter, the synthesizer, all necessary voltage-controlled oscillators, all loop filters, the voltage regulators, the voltage-controlled crystal oscillator, and the power amplifier controller. The chip meets all GSM specification. The design was done in a BiCMOS SiGe 0.35-μm technology and the die area is 14 mm2.
Keywords: BiCMOS technology; GSM-GPRS quad-band application; IQ modulator; Crystal oscillator; Differential Gilbert-cell mixers; Direct conversion receiver; Frequency synthesizer; Fully integrated zero-IF transceiver; Loop filters; Offset mixer; Phase-locked loop; Power amplifier controller; Voltage regulators; Voltage-controlled oscillators